2017
DOI: 10.1016/j.chroma.2017.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Mild extraction methods using aqueous glucose solution for the analysis of natural dyes in textile artefacts dyed with Dyer’s madder ( Rubia tinctorum L.)

Abstract: 8Madder (Rubia tinctorum L.) has been widely used as a red dye throughout history. Acid-sensitive colorants present in 9 madder, such as glycosides (lucidin primeveroside, ruberythric acid, galiosin) and sensitive aglycons (lucidin), are 10 degraded in the textile back extraction process; in previous literature these sensitive molecules are either absent or present 11 in only low concentrations due to the use of acid in typical textile back extraction processes. Anthraquinone aglycons 12 alizarin and purpurin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Although the coloring components and tinctorial properties of these species of Rubia differ significantly, the term 'madder' has been used historically to indicate colorants extracted from them all [38,39]. Out of 68 anthraquinoid compounds detected in madder roots of the various species [40], only a few have been identified in madder-dyed historical textiles [32,38,41,42]. Alizarin [50,51,54].…”
Section: Plant Anthraquinonesmentioning
confidence: 99%
“…Although the coloring components and tinctorial properties of these species of Rubia differ significantly, the term 'madder' has been used historically to indicate colorants extracted from them all [38,39]. Out of 68 anthraquinoid compounds detected in madder roots of the various species [40], only a few have been identified in madder-dyed historical textiles [32,38,41,42]. Alizarin [50,51,54].…”
Section: Plant Anthraquinonesmentioning
confidence: 99%
“…Lucidin is the only commonly reported anthraquinone detected in the roots of Rubia tinctorum to contain a primary alcohol, which could make its degradation unique. As described in our previous research [15], use of the 37% hydrochloric acid: methanol: water (2: Herein it is suggested that when such acidic methods of extraction are used to solvate the dye compounds, degradation of the aglycon lucidin may also occur. The purpose of the research described is to study the degradation of lucidin under the conditions of extraction involved with the common 37% hydrochloric acid: methanol: water (2:…”
Section: Introductionmentioning
confidence: 99%
“…xanthopur purin (7) munjistin (6) no rdamnacanthal (5 ) luci din 4 Only relatively recently has there been significant evidence confirming the primary anthraquinone components in Rubia tinctorum roots as the glycosides ruberythric acid (1) and lucidin primeveroside (3) [10][11][12][13][14]; the majority of literature has pointed to alizarin (2) as the major anthraquinone present, and whilst it does occur in the plant, it is in much lower concentrations than its glycoside [11,12,14]. We have previously suggested [15] that acidic conditions used in extraction and analysis of dyes in previous studies may have led to observations that alizarin was the primary component, it being the product of ruberythric acid hydrolysis (12). However, despite high concentrations of lucidin primeveroside (3) in Rubia tinctorum roots [11,12,14], the aglycon lucidin (4) is rarely detected (and then only in low and trace concentrations in planta and in textile artefacts [10][11][12]16]) even when acidic conditions are used that would promote hydrolysis (34); it is suspected that the reactive nature of lucidin means that it is readily converted to other compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve these problems, the optimal conservation measures should be taken to rid the inappropriate fragment sand improve the properties of textile objects for the long-term stability [2],thereby to slow down the rate of the further deterioration of hemp artifacts as much as possible [3].There is no universal protective measure for all textiles, normal conservation measures include cleaning dust and stains, pre-reinforcement of colored painting, xing separate parts, supporting weak and damaged areas with new fabrics using stitching techniques, and so on. Previous reports mainly focus on the degradation of historical textiles [4][5][6][7], the preservation environment of archaeological textiles [8,9], identi cation of dyestuffs in historical textiles [10][11][12][13], examination of cellulose textile bers [14], fungal contamination of textile objects [15], and textile cleaning [16].…”
Section: Introductionmentioning
confidence: 99%